Evaluasi Pengaturan Pidana Penjara Seumur Hidup Pasca Berlakunya Undang-Undang Nomor 1 Tahun 2023 - Hamidah T Hamidah T; Sunardi Purwanda; Khaerul Mannan; Johamran Pransisto; Aksah Aksah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the provisions on life imprisonment in Law No. 1 of 2023 on the Criminal Code, particularly regarding the absence of a time limit for the review of life-sentenced prisoners. This study employs a normative legal research method using a statutory approach, a conceptual approach, and a comparative approach. Legal materials were analyzed qualitatively using a descriptive-analytical method. The results of the study indicate that although the National Criminal Code has updated the sentencing system to accommodate more humane sentencing objectives, the provisions regarding life imprisonment still leave a normative gap concerning the evaluation mechanism. Unlike the death penalty, which provides for a ten-year evaluation period, life imprisonment lacks a similar mechanism, potentially leading to legal uncertainty and contradicting the principles of rehabilitation and social reintegration. Therefore, a reformulation of the regulations governing the evaluation of life imprisonment is necessary as part of the reform of national criminal law.